The World of Words : Vocabulary for College Success - Richek, Margaret (Boston Wadsworth/Cengage Learning, 2011)
Synopsis: This time-tested, top-selling vocabulary textbook not only teaches students the vocabulary they need for academic success but also provides them with the tools to acquire new words independently for years to come. A wealth of easy to use and engaging exercises offers in-depth word practice. A focus on three critical skills--dictionary use, context clues, and word elements--builds lifelong word acquisition skills. New online audio exercises hone pronunciation, and an abundance of support materials, including pre-written online tests for every chapter, make life a little easier for instructors.
Include Index.
Vocabulary for College Success.
Keywords: Vocabulary -- Vocabulary--Study and teaching